Characteristics of Women in the Qur'an (Analytical Study in Tafsir Al-Azhar and Tafsir Al-Misbah) - Mohammad Fattah; Sitta Rahmi Novita (al-Afkar, Journal For Islamic Studies, 2024)
In the view of Islam, women are people who are highly respected. Al-Qur'an proves the nobility of women in a special sura named Al-Nisa>’ which means woman or woman. Rasulullah SAW also explained that heaven lies in the soles of women's feet, because in women there is a soft heart that causes women's characters to be different from men's. Based on the Al-Qur'an and Hadits, women have a big role in the life of the Al-Qur'an and are never separated from matters relating to women. This is evidenced by the many words used to describe women. Apart from the background above, the author examines the characteristics of women in surah al- al-Tahri<m verses 10,11 and 12 according to Buya Hamka in Tafsir Al-Azhar and M. Quraish Shihab in Tafsir Al-Misba>h as the main source of interpretation. In this study the authors used a qualitative approach which was classified into library research using descriptive data analysis methods. From the results of the research, the authors conclude that: Characteristics are formed not because of who one lives with, not because the family is respectable, so one's good or bad depends on one's piety to Allah swt. Indeed, guidance only comes from Allah SWT, even if he is the wife or husband of a believer. A person who is disobedient and treacherous will still receive punishment from Allah SWT, as well as a believer will not reduce his faith even though he lives with an unjust person. And a person who holds fast to religion and believes in what Allah SWT has decreed for him will be safe. In the analysis I did in the book Tafsir Al-Azhar and Tafsir Al-Misba>h both commented like this.